Safeguarding Access to Justice in the Age of the Online Court. - Denvir, Catrina; Selvarajah, Amanda Darshini (Modern Law Review, 2022)
In 2016 Her Majesty's Courts and Tribunals Service embarked on a significant modernisation programme with a view to developing online courts. In pursuit of this ambition the Courts and Tribunals (Online Procedure) Bill seeks to introduce new procedural rules to govern the online jurisdiction, giving the Lord Chancellor and an Online Procedure Rule Committee the power to mandate which proceedings will be conducted online and what assistance will be provided to users. In this study we analyse survey data and case decisions to highlight the importance of channel plurality and digital support in light of the shift to online courts. Our findings identify the groups most at risk of digital exclusion, and the expectations the judiciary sets in relation to internet access, capability, and the design of online systems. We conclude by detailing what our findings mean for safeguarding access to justice in the digital age.